Platelet-rich plasma application in chondrogenesis - Azadeh Kabiri (Advanced Biomedical Research, 2014)
Platelet-rich plasma (PRP), an autologous derivative of whole blood, has been recently used in surgical treatment. PRP contains growth factors including transforming growth factor-β (TGF-β), insulin-like growth factor (IGF), platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), and vascular endothelial growth factor (VEGF) and also bioactive proteins that influence the healing of tendon, ligament, muscle, and bone. This article describes the current clinical applications of PRP in chondrogenesis. This study reviews and evaluates the studies that have been published in the field of chondrogenesis. All aspects of using PRP in chondrogenesis are reviewed.